Analysis of Phonska Fertilizer Product Quality Control Using Seven Tools Method With Fmea: A Case Study - Ariestiyani, Fitria Novi; Safirin, Moch. Tutuk (Newinera Publisher, 2025)
This study aims to analyze the quality control of Phonska fertilizer products at Phonska Warehouses II and III of PT Petrokimia Gresik using the Seven Tools and Failure Mode and Effects Analysis (FMEA) methods. Seven Tools are used to identify and map the root causes of production defects through Pareto diagrams, cause-and-effect diagrams, and control charts, while FMEA is used to measure and mitigate potential failures in the production process. The study was conducted during the period April to October 2024 with product defect data collected and analyzed. The results showed that the main defects were no coating oil (34%) followed by mesh (29%), caking (24%), and no color pigment (13%). The implementation of corrective steps based on Seven Tools and FMEA has proven effective in reducing product defects to increase production efficiency and the quality of Phonska fertilizer.